RETRACTED: Potential effects of elevated temperature on seasonal movements in slipper lobsters, Scyllarides latus (Latreille, 1803), in the eastern Mediterranean - GOLDSTEIN, JASON SETH; SPANIER, EHUD (Mediterranean Marine Science, 2020)
RETRACTED: Potential effects of elevated temperature on seasonal movements in slipper lobsters, Scyllarides latus (Latreille, 1803), in the eastern Mediterranean Original article: GOLDSTEIN, J., & SPANIER, E. (2020). Potential effects of elevated temperature on seasonal movements in slipper lobsters, Scyllarides latus (Latreille, 1803), in the eastern Mediterranean. Mediterranean Marine Science, 21(2), 482-492. doi:https://doi.org/10.12681/mms.22074 Editor’s Note: This Article has been retracted; the Retraction Note is available at: http://dx.doi.org/10.12681/mms.25854